FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KINERJA TENAGA KESEHATAN DI KLINIK HUSADA JOMBANG - Pratiwi, Widhya Endah; A'yun, Sofa Qurrata; Sulianto, Bagus; Febrianto, Kiki (PRIMA WIYATA HEALTH, 2025)
Background: Efforts to improve the performance of health workers at the Husada Clinic, Jombang are significant and have become a demand because of various aspects related to efforts to improve health services. To achieve good performance, these efforts must be carried out in an integrated and multi-disciplinary manner and involve all related health workers. Objectives: The purpose of this study was to analyze factors related to the performance of health workers at the Husada Clinic, Jombang. Methods: This study used a descriptive research method with a quantitative approach, the sampling method uses a total sample with a total sample of 10 samples. The sample in this study is the health workers at the clinic. The analysis techniques used were Univariate analysis and Bivariate analysis. Results: The results of this study show that health workers who have D3 education as many as 70% of 10 respondents, 80% of training that is attended ≤ 1 time, 80% of facilities that are not available, 60% of motivation that is very lacking, and facilities are the most powerful factor affecting the performance of patients at Husada Clinic, Jombang. The results of the above study concluded that the performance of health workers can be influenced by educational, educational, facility, and motivational factors. Conclusion: For this reason, it is recommended to improve the performance of health workers by increasing knowledge and intelligence through support such as adequate facilities so that services are maximized and can provide satisfaction to the community.